Surgical treatment in hallux rigidus: dorsal cheilectomy and Moberg osteotomy - Alberto Macklin Vadell; Martín Rofrano; Andrés Bigatti (Journal of the Foot & Ankle, 2022)
Dorsiflexion osteotomy of the proximal phalanx of the hallux was popularized by Moberg. The combination of this technique with dorsal cheilectomy of the first metatarsal head showed good results in the surgical treatment of both mild and severe hallux rigidus. In our opinion, the combination of both techniques is the first choice for the surgical treatment of hallux rigidus. Level of Evidence V; Case Report; Expert Opinion.